Serum Beta-Trace Protein versus Glomerulus Filtration Rate as a Predictor for Kidney Function among Hypertensive Patients - Ranisa Handayani; Yuyun Widaningsih; Fitriani Mangarengi; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Beta-Trace Protein (BTP) is a low-molecular-weight glycoprotein that can convert prostaglandin H2 into prostaglandin D2 and is associated with the vascular function's alteration. Serum beta-trace protein has been proposed as a promising marker in predicting kidney function in hypertensive patients. This study aimed to analyze the correlation between BTP and glomerulus filtration rate, particularly in hypertensive patients. A cross-sectional survey was conducted on 70 hypertensive participants admitted to Dr. Wahidin Sudirohusodo Hospital from July-August 2019. Beta-trace protein, serum urea, creatinine, blood pressure, and anthropometric were measured. The Glomerulus Filtration Rate (GFR) with Cockcroft Gault was graded using GFR stages. The hypertension was graded according to the category of the European Society of Cardiology (ESC) 2018. A descriptive test, Kruskal-Wallis test, Fisher exact test, Spearman correlation test, and logistic regression test were performed at a confidence level of 95%. Significant differences were found between the age, systole, diastole, blood urea, creatinine, and GFR (p=< 0.05). There was a significant difference between GFR and the degree of hypertension (p=< 0.001), but no differences were found in the mean value of BTP and the degree of hypertension (p=0.348). A significant negative correlation was found between GFR and BTP (p=0.028, r = -0.263). Logistic regression test s showed that the increased BTP led to 2.591 times greater possibility of end-stage renal disease with GFR < 15 mL/min/ 2 1.73 m (crude odds ratio 95% CI 1.168-5.475). Serum beta-trace protein possesses a prognostic ability of glomerulus filtration rate and can be used to predict the odd of end-stage renal disease in hypertensive patients.